Preventive effect of celecoxib use against cancer progression and occurrence of oral squamous cell carcinoma - Chiang, Shang-Lun; Velmurugan, Bharath Kumar; Chung, Chia-Min; Lin, Shu-Hui; Wang, Zhi-Hong; Hua, Chun-Hung; Tsai, Ming-Hsui; Kuo, Tzer-Min; Yeh, Kun-Tu; Chang, Pei-Ying; Yang, Yi-Hsin; Ko, Ying-Chin (Scientific reports, 2017)
Overexpression of cyclooxygenase-2 in oral cancer increases lymph node metastasis and is associated with a poor prognosis. The potential of celecoxib (CXB) use is reported in cancer treatment by inhibiting proliferation through apoptosis, but the effects on the epithelial-mesenchymal transition (EMT) and cancer cell mobility remain unclear. We performed a preclinical study and population-based study to evaluate CXB use in the prevention of oral cancer progression and occurrence. The in - vitro findings showed that CXB is involved in the inhibition of EMT and cell mobility through blocking transcription factors (Slug, Snail and ZEB1), cytoplasmic mediators (focal adhesion kinase (FAK), vimentin and β-catenin), cell adhesion molecules (cadherins and integrins), and surface receptors (AMFR and EGFR). The murine xenograft model showed a 65% inhibition in tumour growth after a 5-week treatment of CXB compared to placebo. Xenograft tumours in placebo-treated mice displayed a well-to-moderate/moderate differentiated SCC grade, while those from CXB-treated mice were well differentiated. The expression levels of membrane EGFR, and nuclear FAK, Slug and ZEB1 were decreased in the xenograft tumours of CXB-treated mice. A retrospective cohort study showed that increasing the daily dose and medication time of CXB was associated with oral cancer prevention. The findings provide an alternative prevention strategy for oral cancer development with CXB use.